A novel inorganic proton exchange membrane based on self-assembled HPW-meso-silica for direct methanol fuel cells - Lu, J.; Tang, H.; Lu, S.; Wu, Hongwei; Jiang, San Ping (The Royal Society of Chemistry, 2011)
Direct methanol fuel cells (DMFCs) based on high-temperature (100-300 C) proton exchange membranes (HT-PEMs) offer significant advantages over the current low-temperature DMFCs based on perfluorosulfonic acid (e.g., Nafion), such as reduction in CO poisoning via faster reaction kinetics, thus increasing the energy efficiency and reducing precious metal loading. This paper reports a novel inorganic proton exchange membrane based on 12-tungstophosphoric acid mesoporous silica (HPW-meso-silica) nanocomposites. The HPW-meso-silica was synthesized via a one-step selfassembly route assisted by a triblock copolymer, Pluronic P123, as the structure-directing surfactant. The threshold of the HPW content in the nanocomposites for the conductivity of mesoporous silica is 5 wt%. The best results were obtained at 25 wt% HPW-meso-silica, delivering a high proton conductivity of 0.091 S cm1 at 100 C under 100% relative humidity (RH) and 0.034 S cm1 at 200 C under 3% RH and a low activation energy of 14.0 kJ mol1. The maximum power density of a cell with a 25 wt% HPW-meso-silica membrane is 19 mW cm2 at 25 C and increased to 235 mW cm2 at 150 C in methanol fuel.